Perioperative factors influencing post-appendectomy outcomes in adults: a single-center prospective study in the North of Palestine - Alaa Zayed; Khaled Demyati; Abdulsalam Alkaiyat; Alaa Omari; Eliana Masri; Zain Saqfalhait; Yazan.N.A.Abdallah; Obayda Darawsha; Mohammed Hajhamad (BMC Surgery)
Abstract Background Acute appendicitis is one of the most common surgical emergencies, predominantly affecting young adults who form the backbone of the workforce. While its diagnosis and treatment are well-studied, limited research exists on the perioperative factors affecting post-operative outcomes and health-related quality of life in resource-limited settings like Palestine. Understanding these factors is essential to enhance patient care and recovery. Methods This prospective, single-center observational study was conducted at Secondary Surgical Hospital, Nablus, Palestine, from April 2021 to February 2022. Patients aged ≥ 18 years diagnosed with acute appendicitis and treated surgically were included. Data were collected using structured forms covering preoperative (sociodemographics, clinical characteristics, imaging, and laboratory findings), intraoperative (timing, technique, and surgical findings), and postoperative (pain using Visual Analogue Scale), complications, and Health-Related Quality of Life using European Quality of Life-5 Dimensions-3 Levels variables. Follow-ups were conducted at discharge, one week, and two weeks post-surgery. Statistical analyses were performed using SPSS, with p < 0.05 considered significant. Results Ninety-three patients participated, with a mean age of 31.14 years (63.4% ≤ 31 years, 65.6% male). Sociodemographic factors, including smoking (41.9%), educational level (76.4% grade 12 or less), and COVID-19 history (18.3%), were significantly associated with post-operative outcomes. Complicated appendicitis was observed in 43.3% of cases, particularly in older patients and those with delayed presentation (> 48 h, 16.3%). Pain was assessed postoperatively with scores that were significantly higher in females (VAS > 7, p < 0.001) and showed gradual improvement within 24 h post-surgery. Health-Related Quality of Life improved significantly over two weeks, with the European Quality of Life-5 Dimensions-3 Levels index rising from 0.569 at discharge to 0.827 at two weeks. Gender, age, and delayed presentation were strongly associated with worse outcomes, including increased anxiety, reduced mobility, and prolonged recovery. Conclusion Perioperative factors such as age, gender, smoking, educational level, and pre-hospital delay significantly impact pain and HRQoL after appendectomy. Females and older patients experienced worse outcomes, highlighting the need for tailored care. These findings underscore the importance of addressing sociodemographic disparities and optimizing perioperative management. Tailored surgical planning should prioritize early intervention in high-risk groups such as females, older adults, and patients with delayed presentation to reduce complications and improve recovery. Furthermore, the significant role of anxiety and depression in post-operative outcomes suggests that stress-reduction strategies and mental health support should be integrated into patient care. Future research should aim for longer follow-up and broader populations to establish more comprehensive post-appendectomy care guidelines.